Managing Cancer and Living Meaningfully for Advanced Cancer: A Systematic Review - Shenda Maulina Wulandari; Esti Yunitasari; Tiyas Kusumaningrum (Jurnal Ners, 2020)
Introduction: Managing Cancer and Living Meaningfully (CALM) is a supportive-expressive psychotherapy designed to address such barriers and to facilitate communication of mortality-related concerns in patients facing advanced disease and their primary caregivers.  The study was meant to review the benefits of the CALM psychotherapy on patients with advanced or metastatic cancer and caregivers.Methods: This study was done through a systematic review with The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. It broadly used Scopus, Science Direct, and ProQuest database. The search utilized the Boolean phrases  “cancer”, “living meaningfully”, and “psychotherapy” throughout the title, abstract, or keywords. The consideration criteria in the literature study were: an original article, the source from journals, article in English, and available in full text. We obtained 97 articles, and 11 were considered relevant for this systematic review.Results: The findings from the results of this study are that CALM has several psychological benefits for patients with advanced cancer, including: can reduce anxiety and depression, relieve distress, promote psychological growth and well-being, and improve quality of life. Based on these findings, it can be concluded that the CALM psychotherapy has many benefits for patients with advanced cancer and their caregivers and can be used as additional therapy to improve the quality of life to face the end-of-life.Conclusion: CALM may be a feasible intervention to benefit patients with advanced cancer. It may help them overcome obstacles in communication and alleviate death-related distress.